Penafsiran Ayat-Ayat Tentang Sabar - Anisa Fitri; Sowfiah Handini Dwi Wan Tri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article seeks to explore two important concepts: the essence of patience and its relevance within the context of human life, particularly through education. Patience is not merely a virtue; it is an internal state that plays a crucial role in determining the achievement of our life goals. It embodies the ability to organize, control, and direct our behaviors, emotions, and actions while effectively navigating various challenges. This entails approaching problems with both clarity and a broad perspective to find comprehensive solutions. Additionally, a holistic view of issues enables us to see their interconnectedness. The significance of patience can be observed in the actions of both educators and learners, starting from the very beginning of the educational journey, whether at home or in school. The patient attitudes cultivated by both teachers and students are vital keys to achieving success and fulfilling life’s objectives.